2009
DOI: 10.3233/thc-2009-0553
|View full text |Cite
|
Sign up to set email alerts
|

A review of the role of assistive technology for people with dementia in the hours of darkness

Abstract: Assistive Technology (AT) has been utilized to support people with dementia (PwD) and their carers in the home. Such support can extend the time that PwD can remain safely at home and reduce the burden on the tertiary healthcare sector. Technology can assist people in the hours of darkness as well as during the day. The objective of this literature review is to evaluate reported healthcare technologies appropriate to night time care. This paper summarises and categorises the current evidence base. In all, 131 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Monitoring and safety technologies used in dementia care include GPS systems which enable tracking of the person with dementia and alerting the carer if safe boundaries are crossed. Bed Occupancy Sensors are also popular in care settings, allowing monitoring patients by nursing staff [18].…”
Section: A Monitoring and Safetymentioning
confidence: 99%
“…Monitoring and safety technologies used in dementia care include GPS systems which enable tracking of the person with dementia and alerting the carer if safe boundaries are crossed. Bed Occupancy Sensors are also popular in care settings, allowing monitoring patients by nursing staff [18].…”
Section: A Monitoring and Safetymentioning
confidence: 99%
“…3,4 It has been suggested that AT devices offering prompting, reminding and monitoring assistance can function as live-in caregivers in the home-care environment. [5][6][7][8][9][10][11][12][13][14][15][16] However, several factors might influence the use of AT devices. 6 These include accessibility, cost, ethical considerations, the limited and inconsistent evidence that supports AT's benefits, and the low level of perceived usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…This review highlighted a need for more research that focuses on the unique nighttime needs of people with dementia living in their own home. In addition the authors postulated that there is the potential to use technology as a therapeutic intervention in addition to the more traditional applications [22]. In addition Kujala undertook a review exploring the evidence base for user involvement in technology design.…”
Section: Introductionmentioning
confidence: 99%